Evaluation of threshold response and appropriate electrode placement site for electric pulp testing in fluorosed anterior teeth: An in vivo study - Harikumar Vemisetty; Amulya Vanapatla; Polavarapu Venkata Ravichandra; Surakanti Jayaprada Reddy; Rajani Punna; Srujana Chandragiri (Wolters Kluwer Medknow Publications, 2016)
Background: Accurate diagnosis is key to success. Diagnosing the pulpal status in varied clinical situations poses a challenge to the clinician. Electric pulp test (EPT) is one of the valuable attempts in evaluating the sensibility of pulp tissue. The aim of this study was to find out and compare the threshold levels and optimal electrode placement site for EPT in fluorosed and nonfluorosed anterior teeth. Materials and Methodology: Eighty volunteers recruited for this study were divided into two groups based on the incidence of dental fluorosis. Electric pulp testing was done on either of the central incisors in fluorosed and nonfluorosed group. Four sites on each crown were tested 4 times with digitest electric pulp tester, and the mean of the threshold responses was recorded. The data were analyzed with SPSS, version 11. Means of variables from each location were compared using one-way ANOVA and Tukey's post-hoc test while the critical level of significance was set at P < 0.05. Results: The mean and standard deviation of threshold levels in fluorosed teeth were greater when compared to that of nonfluorosed teeth at all sites with incisal edge showing the least mean threshold levels for both the groups (P > 0.05). Conclusion: Within the limitations of this study, it can be concluded that fluorosed teeth respond to higher threshold levels than the non-fluorosed teeth, and incisal edge was the optimal electrode placement site.